Simultaneity in the Scientific Enterprise - Sarafoglou, Nikias; Kafatos, Menas; Beall, John H. (Advances in Social Sciences Research Journal, 2022)
In this article, we explore the concept of simultaneity in the scientific enterprise, defined herein as the near-coincident discovery of significant advances in the development of our scientific understanding of the world. We do this by examining two case studies of such coincident or near-coincident discoveries: the development of the so-called Lorentz transformation by H.A. Lorentz (1904) and A. Einstein (1905); and the Aharonov-Bohm effect discovered independently in chronological order by Franz(1939), Ehrenberg and Siday (1949) and Aharonov and Bohm (1959). It is now generally acknowledged that the Lorentz transformations were independently developed by both Lorentz and Einstein as they worked on different approaches to solve a similar problem – i.e., the preservation of the form of Maxwell’s equations in coordinate systems moving relative to one another, while the relationship between the Ehrenberg-Siday and Aharonov-Bohm works is still controversial. In our view, these independent discoveries allow some speculation about the nature of human discovery and understanding of scientific truths as they progress through time.